2017
DOI: 10.1016/j.lwt.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the impact of fining agents types, oenological tannins and mannoproteins and their concentrations on the phenolic composition of red wine

Abstract: This paper aimed to evaluate and analyze the effect of five fining agents, commercial tannins and mannoproteins on the pigment, color and tannins composition of a Cabernet Sauvignon red wine. The wines were analyzed 2 d after treatment and immediately after separation of sedimentation. Color was evaluated by spectrophotometry and polyphenols were analyzed by spectrophotometry and HPLC-DAD. The results showed that all treatments affected the phenolic contents of the wine. The most remarkable effects on phenolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…As can be seen from Figure 4, clarification treatments could increase limpidity and decrease the color intensity of wine samples. Some researchers suggested that phenol compounds could be absorbed by fining or filtration, thus influence the color intensity of wine samples [17,37], which was in agreement with this study. For balance and persistence, there was no observed differences in the wine samples.…”
Section: Sensory Evaluationsupporting
confidence: 92%
“…As can be seen from Figure 4, clarification treatments could increase limpidity and decrease the color intensity of wine samples. Some researchers suggested that phenol compounds could be absorbed by fining or filtration, thus influence the color intensity of wine samples [17,37], which was in agreement with this study. For balance and persistence, there was no observed differences in the wine samples.…”
Section: Sensory Evaluationsupporting
confidence: 92%
“…Proteins, which play a key role during the fermentation process and form part of the final composition of the sparkling drinks, may agglomerate, causing turbidity of the beverage with an associated negative impact on consumer acceptance . Therefore, the use of fining agents is important for ensuring the physicochemical stability of the fermented beverages and the prevention of hazes and deposits .…”
Section: Introductionmentioning
confidence: 99%
“…On a comparative study among fining agents in red wine, bentonite showed a greater reduction in the total anthocyanin content in comparison to the control wine, and the mixture of PVPP and casein resulted in a reduction similar to that achieved with bentonite. Furthermore, use of vegetable protein resulted in the smallest reduction in anthocyanin content (Ghanem et al, 2017).…”
Section: Total Anthocyaninsmentioning
confidence: 98%